Avaliação institucional de egressos (alumni) no ensino superior: os programas de pós-graduação da Universidade Federal de Santa Maria (UFSM) - Geloch, Rafaela Butzke (2023)
Graduates are the legacy of Higher Education Institutions (HEIs) for society. Monitoring is strategic for the institution to diagnose the quality of education offered. The general objective of this research is to investigate the practices of internal institutional evaluation of graduates in the Postgraduate Course (PG) at the Federal University of Santa Maria (UFSM). Contrary to studies with graduates, this research, inspired by Paul (2015), had as its object of analysis the internal institutional processes of how PG graduates are evaluated and not actually the result of their evaluation. To this end, understanding is developed about: 1) institutional evaluation and quality practices and policies; 2) the graduates and 3) the CAPES guidelines. The research has an exploratory qualitative approach, characterized as a case study, in Postgraduate programs at UFSM. The collection was through primary data: documents that govern internal and external evaluation policies; and secondary, through three instruments: semi-structured interviews, questionnaires and participant observation. The interviews were carried out with two representatives of the IES (PRPGP and PRP); the questionnaires were sent to the 61 IES PPGs, being answered and valid from 48 programs; and participant observation took place during the “IV Institutional Seminar on Postgraduate Assessment and Planning at UFSM - 2022”. The results of this study allow us to diagnose relevant aspects regarding the evaluation and monitoring of graduates, as it proposes suggestions, as well as contributing to the creation of criteria for monitoring institutionalized graduates at UFSM. Through the data, we learned about the good practices carried out by PPGs and the methods of relating to former students. The results demonstrate that programs that are attractive and beneficial to graduates are those that obtained the best feedback from the questionnaires sent by the programs. Therefore, actions carried out by PPGs are decisive for their relationship with the graduate and, consequently, for evaluating the quality of the education offered. In this way, the results allowed the identification of possible indicators, which aim to construct criteria for developing Institutional Policies for monitoring graduates at UFSM. The study meets the needs of the institution, demonstrating a diagnosis of UFSM Postgraduate Studies and bringing possibilities for the implementation of Institutional Policies to monitor graduates.